2022
DOI: 10.2174/1567202620666221025152325
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cerebral Hypoperfusion-induced Dysregulations of Hyperpolarization- activated Cyclic Nucleotide-gated, KCNQ and G Protein-coupled Inwardly Rectifying Potassium Channels Correlated with Susceptibility and Unsusceptibility to Anxiety Behaviors

Abstract: Background: Cerebrovascular lesions could induce affective disorders; however, the depression- and anxiety-related symptoms caused by chronic cerebral hypoperfusion (CCH) and the roles of different hyperpolarization-activated cyclic nucleotide-gated (HCN), KCNQ and G protein-coupled inwardly rectifying potassium (GirK) channel subunits in these pathological processes have been poorly elucidated so far. Objective: To investigate the behavioral change and the alteration of HCN, KCNQ, and GirK subunits in amygd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…62 , 63 Studies also show that blocking HCN can promote the development of anxiety or depression behaviors. 64 , 65 Therefore, HCN is beneficial for exploring potential drug targets for anxiety therapy. At present, four mammalian subtypes (HCN1–4) have been identified, which are all composed of tetramers.…”
Section: Hcnmentioning
confidence: 99%
See 1 more Smart Citation
“…62 , 63 Studies also show that blocking HCN can promote the development of anxiety or depression behaviors. 64 , 65 Therefore, HCN is beneficial for exploring potential drug targets for anxiety therapy. At present, four mammalian subtypes (HCN1–4) have been identified, which are all composed of tetramers.…”
Section: Hcnmentioning
confidence: 99%
“…Cerebrovascular lesions could induce affective disorders, and the increase of HCN1 and decrease of potassium channel subunit 3 expression in amygdale may be factors to blame for anxiety-like symptom caused by cerebrovascular lesions. 65 Studies also showed that the change in synaptic ultrastructure might be caused by lower BDNF, while the high expression of HCN1 downregulated the synthesis of BDNF mRNA in the brain. 69 Blocking HCN could alleviate anxiety-like behavior of rats by improving learning ability, which might be associated with the overexpression of BDNF–mTOR signaling pathways and synaptic plasticity.…”
Section: Hcnmentioning
confidence: 99%
“…Given the importance of M-current in controlling neuronal excitability, neuronal KCNQ channels have emerged as promising targets for the treatment of various disorders related to hyperexcitability. These include conditions such as acute and neuropathic pain, migraine pain, anxiety, epilepsy, stroke, and traumatic brain injury ( Singh et al, 1998 ; Wua and Dworetzky, 2005 ; Munro and Dalby-Brown, 2007 ; Bierbower et al, 2015 ; Li et al, 2019 ; Vigil et al, 2020 ; Zhou et al, 2022 ). The inhibitory effects of presynaptic KCNQ2/3 channels on neuronal excitability have been partially attributed to their modulation of the release of GABA, the primary inhibitory neurotransmitter in the central nervous system ( Martire et al, 2004 ; Peretz et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%